AI & NLP IN BANKING MARKETING: ENGAGEMENT, PERSONALIZATION, AND COMPLIANCE - Shidore, Suwarna Vinay; Tembulkar, Aparna; Gupte, Rupali Surendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence (AI) and Natural Language Processing (NLP) have become essential technologies in the banking sector, reshaping marketing strategies, enhancing customer engagement, and refining compliance frameworks. This investigation examined the impact of AI-driven personalization and NLP-enhanced customer interactions on engagement and trust in banking services. A structured questionnaire was administered to 150 participants from various demographic backgrounds, concentrating on customer experiences with AI-powered chatbots, recommendation systems, and compliance-related communications in the banking industry. The results indicated that AI and NLP techniques notably improved personalization, bolstered customer trust via compliance-focused communication, and elevated overall engagement. Nonetheless, apprehensions surrounding data privacy and the clarity of regulations remained evident. This study investigates the impact of AI and NLP on banking marketing, emphasizing their ability to enhance customer satisfaction while also addressing ethical considerations.